Biochemical and physiological responses of peach rootstocks against drought stress - Hamayat, Naveed; Hafiz, Ishfaq Ahmed; Ahmad, ouqeer; Ali , Irfan; Qureshi, Abdul Ahad (Journal of Pure and Applied Agriculture, 2023)
Climate change is affecting the peach growing areas of Pakistan, especially semi-arid areas of Pothwar pleatue which has great potential for peach production. Drought is one of the major effects of climate change. Therefore, the present study was conducted to evaluate the response of peach rootstocks (GF- 677, Peshawar Local and Swat Local) under in-vitro drought stress condition, provided by polyethylene glycol (PEG) at various osmotic potential levels. L